Bank safety-oriented culture and lending decisions - Tang, Ning; Kamar, Amina; Lin, Chih-Yung; Lu, Chien-Lin (Journal of Financial Stability, 2023)
This study investigates the effects of bank safety-oriented cultures on loan contracts. We regress stock returns during the 1998 Long-Term Capital Management (LTCM) crisis on these risk-taking characteristics and obtain a residual component to proxy the safety-oriented culture of banks. Our empirical results show that banks with a safety-oriented culture increase the probability of signing a contract with low risk borrowers and that they charge lower loan spreads. We also find that these banks ask for more loan covenants to protect their creditor’s rights. Finally, banks with a safety-oriented culture suffer less from borrowers’ defaults and have higher market responses around the dates of loan announcements. Also, our findings reject the alternative hypothesis that banks with a safety-oriented culture only accept less risky lending due to their conservative risk attitude, thus destroying market value for banks.